1999
DOI: 10.1149/1.1391882
|View full text |Cite
|
Sign up to set email alerts
|

Solid Oxide Fuel Cells with Doped Lanthanum Gallate Electrolyte and LaSrCoO3 Cathode, and Ni‐Samaria‐Doped Ceria Cermet Anode

Abstract: The electrode performance of a single solid‐fuel cell (SOFC) was evaluated using a 500 μm thick La0.9Sr0.1Ga0.8Mg0.2O0.3 (LSGM) as the electrolyte membrane. A doped lanthanum cobaltite, La0.6Sr0.4CoO3−δ was selected as the cathode material, and a samaria‐doped ceria‐NiO composite powder was used as the anode material. The spray‐pyrolysis method was applied for synthesis of the starting powders of the cathode and anode. In this study, different microstructures of the cathode were obtained by varying the sin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(55 citation statements)
references
References 19 publications
(26 reference statements)
1
48
0
1
Order By: Relevance
“…The dried resin was ground, slowly heated (0.5 • C/min) to 450 • C, held at this temperature for 2 h and then heated up to 1000 • C at 10 • C/min and held at this temperature for 24 h. This precalcination step was required (i) to decompose all remaining organic residuals and (ii) to form Ga-containing phases thus avoiding the formation of Ga 2 O 3 that could decompose to Ga 2 O and O 2 at high sintering temperatures. 18 In fact, following this calcination step (24 h at 1000 • C), both perovskite phase and small quantities of SrLaGaO 4 and SrLaGa 3 O 7 were formed. 19 The powders were then ground in an agate mortar and then uniaxially pressed at 300 MPa using a 13 mm cylindrical die.…”
Section: E-mail Address: Polini@uniroma2it (R Polini)mentioning
confidence: 99%
See 2 more Smart Citations
“…The dried resin was ground, slowly heated (0.5 • C/min) to 450 • C, held at this temperature for 2 h and then heated up to 1000 • C at 10 • C/min and held at this temperature for 24 h. This precalcination step was required (i) to decompose all remaining organic residuals and (ii) to form Ga-containing phases thus avoiding the formation of Ga 2 O 3 that could decompose to Ga 2 O and O 2 at high sintering temperatures. 18 In fact, following this calcination step (24 h at 1000 • C), both perovskite phase and small quantities of SrLaGaO 4 and SrLaGa 3 O 7 were formed. 19 The powders were then ground in an agate mortar and then uniaxially pressed at 300 MPa using a 13 mm cylindrical die.…”
Section: E-mail Address: Polini@uniroma2it (R Polini)mentioning
confidence: 99%
“…Aldinger and coworkers 13,14 have studied the preparation of LSGM powders by the Pechini method, which is a versatile sol-gel method that proceeds via the formation of a polymeric resin using citric acid and ethylene glycol. 15 However, sol-gel methods can give LSGM materials containing small amounts of undesired phases such as SrLaGa 3 O 7 , SrLaGaO 4 13 and MgO. 16 Majewski et al 14 showed that sintering temperatures as high as 1500 • C were necessary to prepare pure La 0.…”
Section: E-mail Address: Polini@uniroma2it (R Polini)mentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, the resulting ionic conductivities of LSGM at 700 • C is about four times larger than that of conventional yttria-stabilized zirconia (YSZ) electrolyte [1][2][3] and it is apparent that a significant decrease in the SOFC operating temperature would be an important practical advance. 4 Following the initial discovery, [1][2][3][4][5] numerous experimental studies have been carried out on LSGM materials, which also include the effect of transition-metal doping. [6][7][8][9][10][11] It is generally believed that doping with a transition metal cation is undesirable for the ionic conductor due to the appearance of n-or p-type conduction.…”
Section: Introductionmentioning
confidence: 99%
“…En concreto, varios estudios han mostrado que el compósito LSGM posee una conductividad electrónica más alta que el YSZ 53,54 aunque se ha hecho notar la conductividad iónica equivalente de YSZ a 1000 ºC 55 . Por otra parte, se menciona que el electrolito LSGM combinado con al ánodo Ni/SDC tiene más probabilidades de éxito a una temperatura entre 700-800 ºC 56 . Con esta combinación también se han encontrado rendimientos comparables a 800 ºC considerando como electrolito al compuesto YSZ, como ánodo al compuesto YSZ/ Ni y al compuesto LSM/YSZ como cátodo a 1000 ºC 57 .…”
Section: Celda De Combustible De Carbonatos Fundidos (Molten Carbonatunclassified